(untitled) (Eurasian Journal of Philology Science and Education, 2025)
This article examines a common phenomenon in the literature of the Turkic peoples of the late 19th and early 20th centuries – the motif of "awakening". Based on the works of one of the prominent representatives of Kazakh literature of that period, the poet Mirzhakyp Dulatov, and one of the outstanding poets of Kyrgyz literature, the founder of the written tradition, Osmonaaly Sydykov, the thematic, ideological and social aspects of this motif are analyzed. The concept of "awakening" is interpreted as the revival of the national spirit, the stirring of public consciousness, the pursuit of knowledge, and the struggle for social justice. In the work of M. Dulatov “Oyan, Qazaq!” (Awake, Kazakh!) this motif is articulated through calls for national liberation, education, and cultural progress, aimed at fostering the political and spiritual awakening of a people under colonial oppression. In Sydykov’s poetry, the motif of awakening emerges in reflections on social injustice and in appeals to the people to embrace the ideals of justice and humanism. The article offers a comparative analysis of the two poets’ creative legacies, highlighting their ideological consonance within national literature. It also demonstrates the continuity of the “awakening” motif with contemporary spiritual and cultural processes. The relevance of this research lies in demonstrating how the literary ideas of a past era contributed to the shaping of national consciousness and social development in the present. Furthermore, the findings emphasize the enduring role of literature in revitalizing cultural memory and affirming national identity. Keywords: poetry, poem, artistic method, literary style, «awakening» era.